Learn to pass ANY AWS Certification Exam - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to pass ANY AWS Certification Exam on the first try. Topics include: * AWS Certifications * AWS Certified Cloud Practitioner * AWS Exam Guide * AWS White Papers * AWS Sample Questions * AWS Cloud Shell * AWS Unofficial Questions * AWS Academy.